Effects of a training programme aimed at improving the pro-environmental competency of school children (2021)
Bearing in mind the need to understand and analyze the psychological processes involved in pro-environmental behaviour, in order to mitigate the negative effects of the current global ecological crisis, the aim of the research presented here is to analyze the effects of a pro-environmental competency (PEC) training programme on Colombian children. To this end, a quasi-experimental design was applied to a non-probabilistic sample of 102 subjects, evenly distributed between the experimental and control groups (Mage = 8.13; SDage = 0.496; 43.1% female and 56.9% male), applying the ECOPRO-N scale and structured quantitative observation to measure pro-environmental competency. The results showed an increase in the pro-environmental competency of the experimental group with respect to the control group, specifically in the dimensions Beliefs (d = 0.75), Knowledge (d = 0.91) and Motives (d = 0.32), with the greatest effect observed in the Knowledge dimension. This verifies the effectiveness of the intervention programme in terms of fostering pro-environmental behaviours among Colombian children.